2022
DOI: 10.1155/2022/5775926
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impacts of Change Orders on Performance of Construction Projects in Saudi Arabia

Abstract: The construction industry is one of the most complex industries, and it involves numerous change orders. Change orders often occur in all or some phases of industrial construction work and have a significant impact on the success of the project, its on-time completion, or ultimately, an increase in the estimated cost of the project. Change orders are one of the most frequently common problems facing construction projects in Saudi Arabia. The purpose of this study is to examine the impacts of change orders on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Cost and time, with an average (18 factors) score of 3.2, each superseded quality and scope with average scores of 2.9 and 2.8, respectively. These findings align with past studies on the impact of variation orders on construction projects [68][69][70][71]. FSE also supports this finding, where cost and time obtained average weights of 0.26 and 0.27, while average relative weights for quality and scope were 0.24 and 0.23.…”
Section: Discussionsupporting
confidence: 91%
“…Cost and time, with an average (18 factors) score of 3.2, each superseded quality and scope with average scores of 2.9 and 2.8, respectively. These findings align with past studies on the impact of variation orders on construction projects [68][69][70][71]. FSE also supports this finding, where cost and time obtained average weights of 0.26 and 0.27, while average relative weights for quality and scope were 0.24 and 0.23.…”
Section: Discussionsupporting
confidence: 91%
“…Some of the reported strategies to ensure the proper implementation of safety and environmental laws in construction projects include the use of Building Information Management (BIM) systems to ensure project compliance with the requirements of safety management, by ensuring accident prevention and avoiding personal injury or property damage, as well as environmental management, which is necessary to confirm that projects follow laws and regulations relating to the environment [61]. Additionally, the reported mitigation strategies in the literature that focused on tackling change orders were mainly divided into Design Management (e.g., sufficient stipulated time for design and establishment of project management plan), Quality Management (e.g., periodic reviews of project requirements), Documentation Management (e.g., reviewing the sufficiency of contract documents for changes), Financial Management (e.g., detailed breakdowns and pricing of change order components), Dispute Resolution Management (e.g., establishment of a claims and disputes resolution system as set out in the contract), Communication and Relationship Management (e.g., regular meetings between contracting parties to discuss changes), and Procurement Management (e.g., early identification of lead items during design stage), to name a few [62][63][64][65][66].…”
Section: Mitigation Strategies To Tackle Change Orders In Constructio...mentioning
confidence: 99%
“…Saudi Arabia, nowadays, is witnessing a boom in the construction industry in light of 2030 Saudi vision and demand for building millions of housing projects [16,17]. Previous studies showed that 60% of the construction projects are behind schedule because of the inappropriate selection of contractors for construction projects [18]. Another reason might be the cost deviation of construction projects [19].…”
Section: Introductionmentioning
confidence: 99%